The Influence of Zakat, Islamic Corporate Social Responsibility (ICSR), The Sharia Supervisory Board, and The Audit Committe On The Financial Performance of Islamic Commercial Banks in Indonesia - Nurul Hafizza; Nawirah Nawirah (Jurnal Akuntansi, 2025)
This research endeavor seeks to inspect the influence of zakat, Islamic Corporate Social Responsibility (ICSR), sharia supervisory board, and audit committee on the financial performance of Islamic commercial banks operating within the Indonesian context. Method: This investigation employs a panel data regression methodology utilizing a quantitative framework. The dataset utilized comprises secondary data extracted from the annual reports of Islamic banking institutions listed in the Financial Services Authority (OJK) on the temporal span of 2017 to 2023. Results and discussion: The outcomes of this research stipulate that ICSR exerts a positive influence on financial performance, whereas corporate zakat, sharia supervisory board, and audit committee do not demonstrate a statistically significant effect. Conclusion: ICSR positively impacts the financial performance of Islamic banking entities, while the variables of zakat, sharia supervisory board, also audit committee lack significance. It is imperative for Islamic banks to augment their social responsibility initiatives to enhance trust and competitive advantage. Keywords:zakat; Islamic Corporate Social Responsibility; sharia supervisory board; audit committee; financial performance